Studi Keragaan Kebun Kelapa Sawit Swadaya di Kabutapen Kubu Raya - Henny Sulistyowati; Sarbino Sarbino; Nur Arifin (Perkebunan dan Lahan Tropika, 2021)
Performance Study of Independent Small Holder Oil Palm Plantation at Kubu Raya Regency. Independent small holder oil palm plantations are small holder oil palm plantations that are not affiliated with any institution. Farmers sell their own produce to local mills directly or through traders. Independent oil palm smallholders are faced with various problems, including limited access to information technology sources, financing, and markets. Independent small holder oil palm plantations in Kubu Raya Regency are facing a bigger problem because most of the plantations are on peatlands, therefore efforts are needed to help these farmers. Efforts that need to be made at this time are the provision of a database of independent small holder oil palm plantations, which so far do not exist. This study aims to obtain data on the performance of independent small holder oil palm plantations in Kubu Raya Regency. Collecting data using the interview method with a questionnaire. The results showed that most of the independent small holder oil palm farmers in Kubu Raya Regency running their business only as a side job so that the management is not optimal. Another obstacle is the difficulty in accessing the market so they are forced to sell their fruit through middlemen. The problem of transportation, namely transportation and inadequate roads, is also one of the causes of the difficulty in marketing the fresh fruit bunch.